Performance evaluation of the Elecsys PIVKA‐II and Elecsys AFP assays for hepatocellular carcinoma diagnosis. Issue 5 (7th May 2022) - Chan, Henry L Y; Vogel, Arndt; Berg, Thomas; De Toni, Enrico N; Kudo, Masatoshi; Trojan, Jörg; Eiblmaier, Anja; Klein, Hanns‐Georg; Hegel, Johannes Kolja; Sharma, Ashish; Madin, Kairat; Rolny, Vinzent; et al.
Abstract: Background and Aims: Prothrombin induced by vitamin K absence‐II (PIVKA‐II) is a serum biomarker linked to hepatocellular carcinoma (HCC), showing superiority to alpha‐fetoprotein (AFP) for early disease detection. We aimed to assess the clinical and analytical performance of the Elecsys® PIVKA‐II immunoassay in diagnosing HCC and evaluate PIVKA‐II's technical performance. Methods: Serum samples from adult cases (i.e. patients with a first‐time HCC diagnosis; n  = 168) and disease controls (i.e. patients without HCC with an at‐risk condition; n  = 208) were assessed. An AFP cut‐off of 20 ng/mL was used to differentiate between HCC cases and disease controls. Clinical performance of the Elecsys PIVKA‐II assay was compared with that of comparator assays (Lumipulse G PIVKA‐II, μ TASWako DCP, ARCHITECT PIVKA‐II) using receiver operating characteristic curve analysis to determine the area under the curve (AUC) values. Results: The Elecsys PIVKA‐II assay compared favorably with comparator assays. Using a 28.4 ng/mL cut‐off, the Elecsys PIVKA‐II assay detected HCC with 86.9% sensitivity and 83.7% specificity. Clinical performance of the Elecsys PIVKA‐II assay (AUC: 90.8%) was equivalent to that of comparator assays (AUC: 88.3–89.6%). Relatively high PIVKA‐II concentrations were observed for cholangiocarcinoma and pancreatic cancer with the Elecsys assay in specificity panel analyses, indicating that high PIVKA‐II concentrations should not be used alone in the absence of other clinical data. Conclusions: The Elecsys PIVKA‐II assay showed good analytical performance under routine laboratory conditions, comparing favorably with comparator assays. These findings support the suitability of the Elecsys PIVKA‐II assay as an aid in HCC diagnosis. Abstract : This multicenter study assessed the clinical and analytical performance of the Elecsys® PIVKA‐II immunoassay (Roche Diagnostics International Ltd) in diagnosing hepatocellular carcinoma (HCC), versus commercially available comparators. Under routine laboratory conditions, the Elecsys PIVKA‐II immunoassay detected HCC with 86.9% sensitivity and 83.7% specificity and the clinical performance (area under the curve [AUC], 90.8%) was equivalent to comparator assays (AUC, 88.3–89.6%). These findings support the suitability of the Elecsys PIVKA‐II immunoassay as an aid in HCC diagnosis.